2004
DOI: 10.1016/j.neuron.2004.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Coincident but Distinct Messages of Midbrain Dopamine and Striatal Tonically Active Neurons

Abstract: Midbrain dopamine and striatal tonically active neurons (TANs, presumed acetylcholine interneurons) signal behavioral significance of environmental events. Since striatal dopamine and acetylcholine affect plasticity of cortico-striatal transmission and are both crucial to learning, they may serve as teachers in the basal ganglia circuits. We recorded from both neuronal populations in monkeys performing a probabilistic instrumental conditioning task. Both neuronal types respond robustly to reward-related events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
563
10
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(620 citation statements)
references
References 63 publications
46
563
10
1
Order By: Relevance
“…This feature distinguishes the TANs from mesostriatal DANs, which are equally responsive to both rewards and their associated cues. In addition, TANs do not show a differential response based on reward probability whereas striatal DA activation reflects a mismatch between expectation and outcome (Morris et al, 2004). (These findings are best described for cholinergic interneurons in the dorsal striatum.)…”
Section: Mesostriatal Cholinergic Neuronsmentioning
confidence: 91%
“…This feature distinguishes the TANs from mesostriatal DANs, which are equally responsive to both rewards and their associated cues. In addition, TANs do not show a differential response based on reward probability whereas striatal DA activation reflects a mismatch between expectation and outcome (Morris et al, 2004). (These findings are best described for cholinergic interneurons in the dorsal striatum.)…”
Section: Mesostriatal Cholinergic Neuronsmentioning
confidence: 91%
“…Indeed, whereas 5-HT inhibits DA release (Kapur & Remington, 1996; potentially via 5-HT receptors in DA cells, Nocjar, Roth, & Pehek, 2002), there is no reciprocal relationship for DA onto 5-HT (Adell & Artigas, 1999). Finally, although DA dips have been repeatedly observed when outcomes are worse than expected (e.g., Bayer & Glimcher, 2005;Hollerman & Schultz, 1998;Morris, Arkadir, Nevet, Vaadia, & Bergman, 2004;Satoh et al, 2003;Schultz, 1999;Ungless, Magill, & Bolam, 2004), the predicted phasic increase in 5-HT during these negative prediction errors has yet to be observed (see Daw et al, 2002), and if it is observed, it is unclear how it would preferentially bias no-go learning in the BG.…”
Section: Model Limitations and Further Neurobiological Considerationsmentioning
confidence: 99%
“…While these regional differences primarily identify a nAChR that offers a potential means for differentially modifying ACh-DA and nicotine-DA interactions in ventral vs dorsal striatum, it is possible that these data might also impact on how synchronized pauses in cholinergic neurons that occur in response to reward-related cues (Morris et al, 2004) govern DA function (Cragg, 2006). Differences (albeit currently unresolved) in affinity for ACh of each receptor type might have some impact on the efficacy or speed (and therefore time window) with which a fall and rise in striatal ACh tone at nAChRs would be detected and impact on striatal DA release following a synchronized pause in ACh neurons.…”
Section: Dominant Role For A6 Subunit In Nac But Not Cpumentioning
confidence: 99%